STUDENT SELF-STUDY AS THE INSTRUMENT FOR SPECIALIST TRAINING IN CONDITIONS OF CREDIT-TRANSFER SYSTEM OF EDUCATION - Коротич, Н.М. (World of Medicine and Biology, 2016)
Training of well-educated and highly qualified medical professionals, capable to perform their independent professional activity with high theoretical knowledge and expertise in their specialty is the important task of higher medical education. This goal can be achieved by the putting accents on student self-study as the significant instrument of training of future medical professionals, as well as the means of mastering the professional skills. The paper elicits the possible types and forms of student self-study in the medical HEI, its value in enhancing the quality of training for medical activities, as well as the significant role of an educator in students’ motivation to self-study.